Urine Xpert MTB/RIF for the diagnosis of childhood tuberculosis - Anna Lena Lopez; Josephine G. Aldaba; Merrylle Morales-Dizon; Jesus N. Sarol; Jedas Veronica Daag; Ma. Cecilia Ama; Patrick Sylim; Aida Salonga; Karin Nielsen-Saines (International Journal of Infectious Diseases, 2019)
Introduction: Xpert MTB/RIF is recommended for the simultaneous detection of tuberculosis (TB) and rifampicin resistance directly from sputum specimens. Since young children cannot always expectorate, we assessed urine as a possible specimen source to diagnose TB in children using Xpert MTB/RIF. Methods: During a field study to enhance childhood TB identification, spot urine samples were prospectively collected from consecutive ambulatory children aged 0 to 14 years presenting with presumptive pulmonary TB in community health centers. Urine Xpert MTB/RIF was performed by blinded technicians in 182 samples using 2 ml of unprocessed urine. Results: The mean age of presumptive TB cases was 5.9 years (median 5.4, range 0.1 to 14.7) with more males (113, 62%) compared to females. All urine samples tested negative for Xpert MTB/RIF, regardless of whether concentration was performed or not. Out of these 182 presumptive TB cases, 50 (28%) were clinically diagnosed and 5 (3%) were bacteriologically diagnosed to have TB disease using either sputum or nasopharyngeal aspirate specimens. Conclusions: In this community-based study, urine Xpert MTB/RIF does not appear to contribute to the diagnosis of childhood TB. Keywords: Mycobacterium, Pediatric, Philippines, Diagnostic, GeneXpert TB/RIF, Child